Підстави модернізації устаткування для ударного подрібнення зерна - Коруняк, П. С.; Боровець, В. М. (Видавництво Державного університету "Львівська політехніка", 2000)
In work are considered machines for crushing of shock action rotor and hammer of a type and the analysis their robots is carried spent. By the authors the developed and offered new circuits the equipment for crushing a grain, which simultaneously unite two processes, namely impact and vibration.